Calcifying fibrous tumor of the esophagus: A case report with review of the pertinent literature - Abdullahi A. Sulaiman; Hunter L. Monroe; Dane C. Olevian; Tony El Jabbour (Elsevier, 2023)
Calcifying fibrous tumors (CFTs) are benign mesenchymal lesions primary to many anatomic sites, but are commonly identified in the abdomen, particularly the luminal gastrointestinal (GI) tract, of young or middle-aged adults. The clinical presentation of CFTs is largely non-specific and relegated to the site of origin and, thus, they are often incidentally identified via radiology. CFTs are managed with minimally invasive surgical management and are associated with favorable long-term outcomes. Relative to other GI organs, CFTs arising from the esophagus are seldom reported and only described heretofore in occasional case reports. We report a symptomatic CFT of the upper thoracic esophagus with discussion of clinicopathologic features including radiology, histology and immunohistochemistry and formulation of a differential diagnosis pertinent to mesenchymal tumors of the esophagus that may mimic CFTs. A brief review of other rare reports of esophageal CFTs is also provided.